A Survey on Wireless Sensor Networks Architectural Model, Topology, Service and Security - Mahmud, Tamim Al (Engineering International, 2013)
Recent advancement and grown up technologies has enabled the development and implementation of low-cost, energy efficient and versatile sensor networks. Sensor networks are built up with sensors that have the ability to sense fiscal or environmental property. Assumption can be made that Wireless Sensing Network (WSN) is able to sense environmental conditions at Nano and gaseous level. In this paper, first the system architecture of WSN is described. The network may maintain several architectural protocol and topologies. WSN provides some services which are maintained by layered architecture. Another important issue regarding wireless networking is the security challenges. This work guided to a concept of several security issues and discussion to overcome the challenging issues.